HUBUNGAN ANTARA RISK PERCEPTION, OUTCOME EXPECTANCIES DAN TASK SELF-EFFICACY DENGAN KEPATUHAN ODHA DALAM TERAPI ANTIRETROVIRAL DI PUSKESMAS DUPAK SURABAYA - DWI AYU LESTARI, 131311133015 (2018)
Introduction: The prevalence of adherence of people living with HIV/AIDS (PLWHA) in antiretroviral therapy in indonesia is low. This low level of adherence indicates that many PLWHA are not adherent to antiretroviral therapy, it caused by many factors, one of those factors is motivation. Motivation in PLWHA is influenced by risk perception, outcome expectancies and task selfefficacy. This research was aimed to explain correlation between risk perception, outcome expectancies and task self-efficacy with adherence of People Living with HIV/AIDS in Antiretroviral Therapy. Method: The design of this research was descriptive correlational. The population were 35 people living with HIV/AIDS. The sample were 30 people living with HIV/AIDS choosed by purposive sampling. The independent variable of this research were risk perception, outcome expectancies and task self-efficacy, and the dependent variable was adherence of people living with HIV/AIDS in antiretroviral therapy. This research instrument used demography data, perception questionnaire, outcome expectations questionnaire, HIV-Adherence Self-Efficacy Scale (HIV-ASES) and adherence of antiretroviral therapy questionnaire. Data were analyzed using spearman-rho test with level of significance ≤0,05. Result and analysis: The result showed that there was significant correlation between risk perception (p=0,001), outcome expectancies (p=0,005) and task self-efficacy (p=0,000) had correlation with adherence of people living with HIV/AIDS in antiretroviral therapy. Discussion: It could be concluded that task self-efficacy has the strongest correlation in adherence of people living with HIV/AIDS in antiretroviral therapy. Further research is expected to improve data collection procedure by adding interview method, especially in adherence of antiretroviral therapy questionnaire.